Electrochemical kinetics of Ag|Ag+ and TMPD|TMPD+ in the room-temperature ionic liquid [C4mpyrr][NTf2]; toward optimizing reference electrodes for voltammetry in RTILs - Rogers, E.; Silvester, Debbie; Ward Jones, S.; Aldous, L.; Hardacre, C.; Russell, A.; Davies, S.; Compton, R. (American Chemical Society, 2007)
The voltammetry and kinetics of the AgjAg+ system (commonly used as a reference electrode material in both protic/aprotic and RTIL solvents) was studied in the room-temperature ionic liquid N-butyl-Nmethylpyrrolidinium bis(trifluoromethylsulfonyl)imide, [C4mpyrr][NTf2] on a 10 ím diameter Pt electrode. For the three silver salts investigated (AgOTf, AgNTf2, and AgNO3, where OTf- ) trifluoromethanesulfonate, NTf2 - ) bis(trifluoromethylsulfonyl)imide, and NO3 - ) nitrate), the voltammetry gave rise to a redox couple characteristic of a “deposition/stripping” process at the platinum electrode surface. Using potential step chronoamperometry, the diffusion coefficients of AgOTf, AgNTf2, and AgNO3 were found to be 1.05, 1.17, and 5.00 10-11 m2 s-1. All three voltammograms were theoretically modeled to reveal surprisingly slow standard electrochemical rate constants, k0, of 2.0, 1.5, and 0.19 10-4 cm s-1 respectively for the Ag+jAg0 couple. As a potentially faster alternative to the AgjAg+ system, the voltammetry and kinetics of the TMPDjTMPD+¥ system (where TMPD ) N,N,N ¢,N¢-tetramethyl-p-phenylenediamine) was also studied, using neutral TMPD and two TMPD radical cation salts, with BF4 - and NTf2 - counter anions. Diffusion coefficients for TMPD, TMPD+¥BF4 -, and TMPD+¥NTf2 - were calculated to be 1.84, 1.35, and 1.43 10-11 m2 s-1 respectively, and a k0 value of 2.6-2.8 10-3 cm s-1 was obtained from theoretical fitting of the cyclic voltammetry. This number is an order of magnitude larger than that for the AgjAg+ system, allowing for the suggestion that the TMPDjTMPD+¥ system may be more suitable than the AgjAg+ system as a redox couple for use in reference electrodes for ionic liquids.